Autologous stem-cell transplantation in patients with mantle cell lymphoma beyond 65 years of age: a study from the European Group for Blood and Marrow Transplantation (EBMT) - Jantunen, Esa; Dreger, Peter (Annals of oncology, 2012)
Abstract. Background: Limited experience is available on the feasibility and efficacy of autologous stem-cell transplantation (ASCT) in patients with mantle ce